Beyond test scores : a better way to measure school quality - Schneider, Jack (Harvard University Press, 2017)
What makes a school a "good" school? It's hard to say, and our current methods of measuring school quality are crude and often misleading. Parents who face the problem of where to matriculate their children are often left to surf websites that only offer one or two metrics by which to measure school accomplishment. Or they ask around among neighbors, work colleagues, and so on; the problem, of course, is that nearly everyone thinks the school their children attend is a "good" school. Lawmakers and education reformers review spreadsheets containing data that only confirm what we already know: high average test scores, the metric most often used to indicate school quality, are merely a reflection of the socioeconomic status of students who attend the school. But which schools improve scores the most? Which are best at protecting kids from bullying and harassment? Which schools are best at science, at the arts? Which schools are best at preparing underserved groups for college and the job market? None of the metrics for school quality that are currently widely available are helpful at answering these questions. Schneider led a team of researchers who asked people what they thought made for a good school. The answers they provided sometimes aligned with the measures policymakers and researchers have deemed important--and sometimes not. Then they set out to design a new system for measuring school quality that would allow Americans to figure out which schools were good at doing what and how to hold schools accountable for improving outcomes.--Resumé vydavatele
Keywords: vzdělávání -- Spojené státy americké; vzdělávací politika -- Spojené státy americké; vzdělávací cíle -- Spojené státy americké; kvalita vzdělávání -- Spojené státy americké; pedagogická evaluace -- Spojené státy americké; didaktické testy -- Spojené státy americké; education -- United States; educational policy -- United States; educational aims -- United States; quality of education -- United States; educational evaluation -- United States; educational tests and measurements -- United States; monografie; monographs